Leuconidae Sars, 1878 (Crustacea: Cumacea) from the southwestern Atlantic, filling the distribution gap along the Brazilian coast - Brito, Ayrton Do Ramo; Serejo, Cristiana Silveira (Zootaxa, 2023)
The family Leuconidae Sars, 1878 is one of the eight widely recognized families of Cumacea and can be found in all oceans, but often in deeper waters (> 200 m). Despite its worldwide distribution, Southwestern Atlantic records were restricted to Argentina and Uruguay, indicating a gap in the knowledge of the group along the Brazilian coast. Samples were collected in the Campos, Espírito Santo and Santos Basins with box core and/or van Veen grabs between 16–3000 m in depth. A total of five new species and a new genus are described herein. Leucon (Alytoleucon) rhuanae sp. nov., Leucon (Crymoleucon) pseudograndidentatus sp. nov., Leucon (Macrauloleucon) watlingi sp. nov., Eudorella helenae sp. nov. and Gyneleucon tripedium gen. et sp. nov. The lack of knowledge on cumacean leuconids along the Brazilian coast is clearly a result of taxonomic impediment. The present study is an effort towards understanding and revealing the Cumacea fauna from the Brazilian margin, bringing new data on the family Leuconidae found in the continental shelf and slope of the Espírito Santo, Campos and Santos Basins, areas with high oil and gas exploration. Promoting the characterization of these areas is essential to a wide understanding of the local species richness and consequently provides tools for preservation and monitoring activities.